The theological use of eating and drinking metaphors in Origen’s De principiis. (2019)
This article focuses on the theological use of the eating and drinking metaphors in Origen’s De principiis. The work is organized in three parts: 1. Physiological convictions regarding eating and drinking, where it is briefly shown how Origen understands this process in a biological approach; this is important because these convictions operate as assumptions within which the Alexandrian constructs his theology. 2. Methodological remarks about the semantic field of eating or drinking, at a level both biblical and cultural; this is important in order to justify the use of these metaphors in theological contexts. Finally, 3. Theological uses of the metaphors, which demonstrate how Origen uses these metaphors to explain and/or clarify important theological issues.